ТHE PROBLEMS OF THE SHADOW ECONOMY IN THE EUROPEAN UNION COUNTRIES - E. Akopyan (Вестник университета)
Globalization and the development of information technologies have dramatically changed the space in which economic entities function and carry out their activities. However, despite all the advantages of modern technology and the fact that they allow to save transaction costs, many enterprises are still prone to the use of cash in the implementation of various types of transactions. Transactions served in cash are easy to hide and not to declare, thus generating one of the most destructive phenomena in the society - the shadow economy, which includes activities deliberately concealed from the state authorities. The study of problems of the shadow economy growth and the identification of major reasons for it in the European Union countries is presented.